UPAYA MENINGKATKAN MOTIVASI BELAJAR AQIDAH AKHLAK SISWA KELAS V MI ISLAMIYAH MELALUI METODE REWARD DAN PUNISHMENT - Wardani, Federika; Khoiroh, Aifi Umdatul; Munawir (Kurikula : Jurnal Pendidikan, 2024)
The low motivation to learn Aqidah Akhlak among students of Class V MI Islamiyah is a very concerning thing. This can affect students' understanding of religious and moral values that are important for their character development. This study aims to determine the effect of reward and punishment methods in increasing the learning motivation of class V students at MI Islamiyah in the subject of Aqidah Akhlak. Data collection techniques used in this study include tests, observations, and field notes, then the data obtained is analyzed using qualitative descriptive. The results of the study showed the influence of reward and punishment methods with differences in the average cognitive value and the average motivation value of students. Before using the reward and punishment method, the average cognitive value was 74 and the average motivation value was 68%. The average cognitive value after applying the reward and punishment method increased to 88 and the increase in the average motivation value was 86%. Based on this, it can be concluded that learning using the reward and punishment method can increase the motivation to learn Aqidah Akhlak in class V MI Islamiyah.